#nomakeupselfie: The impact of natural no-makeup images and positive appearance comments on young women's body image. (September 2020) - Politte-Corn, Madison; Fardouly, Jasmine
Highlights: Ideal images and no-makeup images decreased facial satisfaction. Ideal images but not no-makeup images decreased overall appearance satisfaction. No-makeup images are more attainable that ideal images. More appearance comparisons are made to ideal images than no-makeup images. Positive appearance-related comments did not impact body image. Abstract: Presenting no-makeup selfies interspersed with idealized made-up images may be beneficial for women's body image. However, the impact of viewing only no-makeup selfies is still unknown, as is the influence of any positive appearance-related comments from others accompanying those images on social media. Thus, in the present study, we examined the impact of viewing either: (1) idealized images with appearance-related comments, (2) idealized images with appearance-neutral comments, (3) no-makeup images with appearance-related comments, or (4) no-makeup images with appearance-neutral comments, on young women's ( N = 394) appearance satisfaction, mood, appearance comparison frequency, and perceived attainability. Viewing idealized selfies of attractive women reduced women's satisfaction with their overall and facial appearance. Viewing natural no-makeup images of those attractive women also reduced women's facial satisfaction but had no impact on overall appearance satisfaction. No-makeup selfies resulted in less frequent appearance comparisons and higher perceived attainability than idealized images. There was no impact of appearance-related comments on any of the outcomes. The results suggest that no-makeup images are less detrimental to young women's body image than idealized images.